Fusarium head blight in wheat: characteristics of the disease and possibilities of using predictive models for optimizing fungicide use - Mazzilli, S.; Pérez, C.; Ernst, O. (Agrociencia Uruguay, 2007)
Fusarium head blight (FHB) is one of the most important diseases affecting wheat (Triticum aestivum L.) and other small grain species worldwide. The combination of epidemiological characteristics of the pathogen, the lack of effective genetic resistance in commercial cultivars, and the strong effect of the environmental factors make the implementation of integrated management to reduce FHB epidemics desirable. The etiology and epidemiology aspects of FHB are analyzed as well as different management practices designed to reduce the impact of this disease. Special emphasis is made on chemical control and the development of predictive models to optimize the timing of fungicide applications.